2003
DOI: 10.1155/edr.2003.205
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin‐Like Growth Factor System

Abstract: The insulin-like growth factor (IGF) system in ubiquitous and plays a role in every tissue of the body. It is comprised of ligands, receptors and binding proteins, each with specific functions. While it plays an essential role in embryonic and post-natal development, the IGF system is also important in normal adult physiology. There are now numerous examples of diseases such as diabetes, cancer, and malnutrition in which the IGF system is a major player and, not surprisingly, there are attempts to affect these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(106 citation statements)
references
References 90 publications
1
99
0
6
Order By: Relevance
“…Global activation of IGF-IR signaling and loss of negative feedback to IRS-1 appear to be reprogrammed in endometrial hyperplasia (18). IGF1R is overexpressed in the majority of malignant tissues, where it binds IGF to function as an anti-apoptotic agent by enhancing cell survival (19,20). In the present study, downregulation of IRS1 and IGF1R was detected upon ARID1A depletion in HEC-1-A cell lines.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Global activation of IGF-IR signaling and loss of negative feedback to IRS-1 appear to be reprogrammed in endometrial hyperplasia (18). IGF1R is overexpressed in the majority of malignant tissues, where it binds IGF to function as an anti-apoptotic agent by enhancing cell survival (19,20). In the present study, downregulation of IRS1 and IGF1R was detected upon ARID1A depletion in HEC-1-A cell lines.…”
Section: Discussionsupporting
confidence: 50%
“…IGF1 and IGF2 are strong mitogens that exert proliferative and anti-apoptotic effects via 2 downstream signaling pathways, the MAPK/ERK and phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/protein kinase B cascades (2). The IR, IRS1/2 and MAPK/ERK1/2 signaling pathways have all been revealed to be highly expressed in EC (19,21). Wang et al (21) demonstrated that visfatin stimulated EC cell proliferation by inducing G1/S cycle progression via activation of IR, PI3K/protein kinase B and MAPK/ERK1/2 signaling pathways and consequent upregulation of MYC proto-oncogene, bHLH transcription factor and cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin-like growth factor (IGF) signaling axis includes two IGF ligands (IGF-1 and IGF-2), two receptors (IGF1R and IGF2R) and at least six binding proteins (IGFBP 1-6) (Le Le Roith and Roberts, 2003;Yakar et al, 2005). Deregulated IGF-1 signaling has been associated with the risk of breast, colon, lung, prostate and other cancers (Pollak et al, 2004;Foulstone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone (GH) is the major factor stimulating IGF‐I biosynthesis and release, and IGF‐I mediates many, but not all, of its activities 25, 34. The post‐natal growth of bone and muscles depends on pre‐ and post‐pubertal levels of IGF‐I 35.…”
Section: Igfs and Igfbp‐6 Have Multiple Important Functionsmentioning
confidence: 99%